RESOLUSI KONFLIK LAUT TIONGKOK SELATAN DALAM MENJAMIN KEAMANAN PERDAGANGAN BEBAS DI KAWASAN ASIA TENGGARA - Muhammad Fardi Sofari (Penerbit Lafadz Jaya, 2026)
This study examines the dynamics of the Indonesia–China relationship within the context of the South China Sea dispute, particularly in the North Natuna Sea, and evaluates the strategic role of ASEAN in fostering a collective conflict resolution framework. Despite significant economic interdependence, evidenced by China’s position as one of Indonesia’s largest investors, bilateral relations are marked by persistent tensions arising from China’s Nine Dash Line (NDL) claim, which overlaps with Indonesia’s Exclusive Economic Zone (EEZ) under UNCLOS 1982. This research highlights the paradox of cooperative economic engagement alongside geopolitical contestation, emphasizing the implications for Indonesia’s national security and maritime sovereignty. The study further analyzes the strategic importance of the South China Sea for ASEAN, including its role as a global maritime trade route, a repository of vast energy resources, and a center of marine biodiversity. It argues that China’s expansive claims pose not only legal challenges but also threats to regional stability, economic security, and freedom of navigation. However, ASEAN’s effectiveness in addressing the dispute is constrained by internal heterogeneity, as member states adopt divergent approaches ranging from confrontational to accommodative policies toward China. By examining the evolution of ASEAN mechanisms, particularly the Declaration on the Conduct of Parties in the South China Sea (DoC) and the ongoing negotiations of the Code of Conduct (CoC), this study underscores the limitations of existing frameworks and the urgent need for a more binding and enforceable regional agreement. It proposes that ASEAN must strengthen its collective identity through the ASEAN Way while simultaneously adopting a unified stance against unlawful maritime claims. The paper concludes that Indonesia’s leadership, especially during its ASEAN Chairmanship, represents a critical opportunity to consolidate regional solidarity, accelerate CoC negotiations, and ensure a rules-based maritime order. A cohesive ASEAN approach is essential to safeguard regional stability, uphold international law, and protect the shared interests of Southeast Asian nations.